2019
DOI: 10.1002/med.21567
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate, a two‐edged drug: Current status and future directions

Abstract: Dimethyl fumarate (DMF) is a fumaric acid ester registered for the treatment of relapsing‐remitting multiple sclerosis (RRMS). It induces protein succination leading to inactivation of cysteine‐rich proteins. It was first shown to possess cytoprotective and antioxidant effects in noncancer models, which appeared related to the induction of the nuclear factor erythroid 2 (NF‐E2)–related factor 2 (NRF2) pathway. DMF also displays antitumor activity in several cellular and mice models. Recently, we showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
103
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 135 publications
1
103
0
2
Order By: Relevance
“…Dimethyl fumarate (DMF) is the main component of Fumaderm ® (Biogen Idec), a drug which was approved in 1994 in Germany for the treatment of patients suffering from severe psoriasis, and then in 2008 for moderate psoriasis. In 2017, a similar DMF product termed Skilarence ® (Almirall) was approved by the European Medicines Agency for moderate and severe psoriasis [20,51,52]. Psoriasis is a chronic T cell-and DC(dendritic cell)-mediated inflammatory skin disease affecting 2%-4% of the population and plaque psoriasis is the most common type, affecting about 90% of all patients [53].…”
Section: Dmf For the Treatment Of Psoriasis And Multiple Sclerosis (Ms)mentioning
confidence: 99%
See 3 more Smart Citations
“…Dimethyl fumarate (DMF) is the main component of Fumaderm ® (Biogen Idec), a drug which was approved in 1994 in Germany for the treatment of patients suffering from severe psoriasis, and then in 2008 for moderate psoriasis. In 2017, a similar DMF product termed Skilarence ® (Almirall) was approved by the European Medicines Agency for moderate and severe psoriasis [20,51,52]. Psoriasis is a chronic T cell-and DC(dendritic cell)-mediated inflammatory skin disease affecting 2%-4% of the population and plaque psoriasis is the most common type, affecting about 90% of all patients [53].…”
Section: Dmf For the Treatment Of Psoriasis And Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…DMF treatment causes a shift to a Th2 anti-inflammatory type response and DMF-treated patients have fewer circulating immune cells [51,52,[56][57][58]. As a Th1/Th17 cytokine profile is also a characteristic of several other diseases, DMF may be also efficient in patients suffering from diseases such as colitis, Crohn's disease, rheumatoid arthritis or systemic sclerosis [51,57,59]. Indeed, several clinical trials suggest the efficacy of DMF in patients suffering from other inflammatory diseases and cancer ( Table 1).…”
Section: Dmf For the Treatment Of Psoriasis And Multiple Sclerosis (Ms)mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that this compound appears to increase the glycolytic rate [42]. However, high DMF concentrations can downregulate glycolysis by inactivation of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), a rate-limiting enzyme in the glycolytic pathway [47,48].…”
Section: Dimethyl Fumarate Attenuates Os-induced Citotoxicity and Enhmentioning
confidence: 99%